Estimation of IL-6 and IL-8 in the Urine and Serum of Children with Urinary Tract Infection (Indian Journal of Forensic Medicine & Toxicology, 2021)
Urinary tract infection (UTI) is defined as the presence of bacteria in urine along with symptoms of infection.UTIs occurs in 1.1% of girls and 1.4% of boys in the first year of life. The aim of the study was to assessthe usefulness of measurement of pro-inflammatory interleukin (IL)-6 and IL -8 concentrations in the urineand serum of children with UTI. A total of Eighty serum sample and seventy tow urine sample have beencollected from children with urinary tract infection, Their age ranged between 33days- 12 years old, fifty sixchildren of the same age collected as controls .Urine and serum IL-6 and IL-8 concentrations of both groupswere measured and compared. Urine and serum concentrations of IL -8 were significantly higher in childrenwith UTI compared with controls group (P = 0.0001, P = 0.0002) respectively, while there was no significantdifferent in urine and serum concentration of IL-6 of children with UTI and controls group(P = 0.1199 , P=0.572) respectively. The results demonstrate that IL-8 is a good biomarker for urinary tract infection, whileIL-6 is not.
Keywords: urinary tract infection, Interleukin-6, Interleukin-8.